2000
DOI: 10.1889/1.1832849
|View full text |Cite
|
Sign up to set email alerts
|

10.2: A Controlled Lateral Volume Discharge for High Luminous Efficiency AC‐PDP

Abstract: Efficiencies measure greater than 2 lumens/watt in a PDP structure with auxiliary control electrodes creating lateral volume discharges. These sustain discharges can be more efficient than conventional surface discharges because they have a "positive like" column which occurs deeper in the PDP cell and is longer in space and time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…This mechanism allows operation at a reasonable but still large sustaining voltage even for very large coplanar gaps (more than 500 µm at 500 torr). This two-phase lateral volume discharge has been presented elsewhere 11 and simulations 12 clearly show the role of the data electrode in the triggering of the main discharge between coplanar electrodes.…”
Section: Long-coplanar-gap Configurations With Auxiliary Electrodesmentioning
confidence: 64%
See 1 more Smart Citation
“…This mechanism allows operation at a reasonable but still large sustaining voltage even for very large coplanar gaps (more than 500 µm at 500 torr). This two-phase lateral volume discharge has been presented elsewhere 11 and simulations 12 clearly show the role of the data electrode in the triggering of the main discharge between coplanar electrodes.…”
Section: Long-coplanar-gap Configurations With Auxiliary Electrodesmentioning
confidence: 64%
“…In order to keep the high efficiency of the large coplanar discharge while lowering the sustaining voltage it seems natural to try to use auxiliary electrodes. Schemerhorn et al 11 proposed an electrode configuration with two powered auxiliary electrodes located between the large-gap coplanar electrodes and in the same plane. The authors mention that these auxiliary electrodes can help initiate, control, or guide the discharge and achieve higher luminous efficacy.…”
Section: Long-coplanar-gap Configurations With Auxiliary Electrodesmentioning
confidence: 99%
“…D. Schermerhorn suggested a new PDP structure having auxiliary electrodes. 5 Extra electrodes between the main electrodes were inserted and a luminous efficacy of 2 lm/W was obtained. L. F. Weber suggested that a high-luminous-efficacy PDP can be attained with a positive column discharge.…”
Section: Long-gap Dischargementioning
confidence: 99%
“…There have been reports [34]- [37] on the possibility of inducing the long discharge path in order to improve the luminous efficiency. The simplest method to make long discharge path is to increase the gap distance between two sustain electrodes [38].…”
Section: B One-auxiliary Electrode Modelmentioning
confidence: 99%